A case report of balloon-assisted tracking to overcome coronary sinus competent valve: a novel technique in left ventricular lead implantation. Issue 2 (2nd February 2022) - Samy, Mohamed; Hamdy, Rehab M
Abstract: Background: Competent lateral and posterolateral valves showed proximal tortuosity that might hinder left ventricular (LV) lead implantation in cardiac resynchronization therapy (CRT). Case summary: A 57-year-old woman was diagnosed as non-ischaemic cardiomyopathy, no other comorbidities, complaining of dyspnoea [New York Heart Association (NYHA) class III], and on optimal medical therapy. Electrocardiogram showed left bundle branch block with QRS duration 150 ms. The patient was candidate for CRT. However, during LV lead implantation, a competent posterolateral vein valve and proximal tortuosity hindered LV lead implantation that was overcome by balloon-assisted tracking technique. At 9 months of follow-up, the patient had NYHA class II, ejection fraction improved to 38%, and all implanted leads were still in place. Discussion: Balloon-assisted tracking technique can be used to cross coronary sinus and smaller veins with competent valves and coronary veins tortuosity.